Outcomes and prognostic factors of primary gastric GIST following complete surgical resection: A single surgeon experience - Chakrapan Euanorasetr (2018)
Objective: To examine the surgical outcomes and to identify prognostic factors influencing tumor recurrence and survival after curative resection of primary gastric GIST as performed by one surgeon. Material and Method: The medical records of patients with primary gastric GIST (c-kit or CD117-positive) who underwent curative resection by one surgeon between January 2001 and March 2009. The clinicopathological features, tumor recurrence, and recurrence-free survival were assessed. Results: Twenty-two patients (10 males and 12 females) with a median age of 66 years (range, 39-98 yrs) were reviewed. According to the NIH risk criteria, high-risk, intermediate-risk and low-risk GISTs were found in 12 (54.5%), one (4.5%), and nine (41%) patients, respectively. After a median follow-up of 42 months (range, 19-96 months), three patients (13.6%) developed tumor recurrence, all of whom had high-risk GIST. No patient died during this follow-up period. The recurrence-free probability at 5 years was 88% (95% CI; 59%-97%). Univariable analysis showed that high mitotic count ( > 5/50 HPF) was a significant predictor of tumor recurrence. Conclusion: Low and intermediate-risk gastric GIST have an excellent prognosis after complete surgical resection alone, while high-risk group are associated with increased disease recurrence despite complete surgical resection. Adjuvant therapy should be advocated for patients with high-risk gastric GISTs. High mitotic count is an important prognostic factor for recurrence after surgery.